PERLINDUNGAN HUKUM KONTRAK KERJA TERHADAP HAK- HAK PEKERJA SPBU DI KABUPATEN MAROS - Alif Sultan; Jumadi; Andi Safriani (Alauddin Law Development Journal, 2019)
Legal protection against legal protection against the protection of occupational safety and health in gas station workers / operators in Maros Regency has not been carried out properly, this can be seen from the lack of application of rules regarding the protection of occupational health and safety for workers / operators of gas stations in Maros Regency and one of the efforts to provide occupational safety and health protection. Implementing a regulation can not be separated from the inhibiting factors in its application. in the implementation of legal protection against the protectionof occupational safety and health in gas station workers in Maros Regency, it has been regulated in the Act even though it has been regulated in the Law the inhibiting factors result in the rights of each worker not being fulfilled. These factors are divided into two, namely internal factors and external factors.